Rosai-Dorfman disease preceding acute myeloid leukemia: an extremely rare case and a literature review - Sara E. Marhoon; Ali H. Ali; Ali Husain; Salma Elashwah; Azza AbdelAziz; Mariam Elias (European Journal of Case Reports in Internal Medicine)
Background: Rosai-Dorfman disease (RDD) is a histiocytic disorder that was recently reclassified as a histiocytic neoplasm. It is characterized by nodal and extranodal involvement. Leukaemia-associated RDD is a rare subtype of neoplasia-associated RDD, particularly when leukaemia precedes RDD, with only one paediatric case reported in the literature. Case report: A 33-year-old woman presented with cervical swelling that had persisted for one month. Ultrasound examination and biopsy confirmed the diagnosis of RDD. The patient subsequently developed raccoon eyes and bilateral eyelid oedema. Laboratory investigations revealed bicytopenia and leukocytosis. Unexpectedly, bone marrow aspirate and flow cytometry confirmed the presence of acute myeloid leukaemia (AML). Following repeated complaints of headache, brain magnetic resonance imaging revealed a callosal lesion, suggestive of a space-occupying lesion. One year later, the patient relapsed and died from septicaemia. Conclusion: This case report describes the progression of RDD to AML in an adult, highlighting the need for long-term follow-up and further research into its pathogenesis to improve outcomes.